Effectiveness of the Ecotropis STEM Approach to Student Forestry Literacy - Fadilah, Dian; Nizaar, Muhammad; Haifaturahman, Haifaturahman; K. Nagy, Emese; Hafeez, Muhammad (Universitas Negeri Makassar, 2025)
This study aims to analyze the potential of applying the Ecotropis STEM approach in improving forestry literacy among elementary school students. Forestry literacy in this study is positioned as part of environmental science literacy that emphasizes conceptual understanding, ecological awareness, and concern for the preservation of forest resources through contextual learning based on tropical ecosystems. The study used a quasi-experimental design with unequal experimental and control groups. The research sample consisted of 41 elementary school students, with 18 students in the experimental class and 23 students in the control class. The research instrument was a 20-item multiple-choice test that had undergone content validation and reliability testing. Data analysis was performed using descriptive statistics, normality tests, and Independent Sample t-tests to compare the learning outcomes of the two groups. The results of the analysis showed that the average posttest scores of students in the experimental class were higher than those in the control class. However, the results of the inferential statistical test showed that the difference was not statistically significant (p > 0.05). These findings indicate that the application of the Ecotropis STEM approach has not been empirically proven to have a significant effect on improving students' forestry literacy, although descriptively there is a tendency for learning outcomes to improve in the experimental group. The insignificant difference in learning outcomes between groups is thought to be influenced by several factors, including the relatively limited sample size, the short duration of the learning intervention, and the adaptation process of teachers and students to the learning approach applied. Therefore, the findings of this study need to be interpreted cautiously as an initial indication of the potential of the Ecotropis STEM approach, rather than as conclusive evidence of its effectiveness. Overall, this study provides an initial contribution to the development of Ecotropis STEM-based learning in primary education and emphasizes the need for further research with a stronger methodological design, longer intervention duration, and larger sample size to obtain more convincing conclusions.